Analysis of the Defective Signal Transduction Mechanism through the Platelet Thromboxane A2 Receptor in a Patient with Polycythemia Vera - Ushikubi, Fumitaka; lshibashi, Takafumi; Narumiya, Shu; Okuma, Minoru (Thrombosis and Haemostasis, 1992)
We previously reported a patient with polycythemia vera whose platelets showed subnormal responses to thromboxane A2 (TXA2) (Thromb Haemostas 1987; 57: 158-64). The patient’s platelets showed normal binding activity to TXA2 analogues but the generation of second messengers was defective. We further studied the mechanism of this dysfunction in this work. The coupling of TXA2 receptor with its relevant GTP binding protein was examined using STA2(a synthetic TXA2 mimetic)-induced augmentation of GTPase activity as its measure. Only subnormal increase in the GTPase activity of the patient’s platelet membrane was found after STA2 stimulation. Down regulation of TXA2 receptor of the patient’s platelet also showed abnormal behavior. These results suggested that the defective coupling of TXA2 receptor with GTP binding protein could be included as a cause of defective signal transduction in this patient’s platelets. This defect might be due to the abnormality of TXA2 receptor itself if the receptor was down regulated by its phosphorylation through agonist-induced conformational change.